(untitled) (Research, Society and Development, 2025)
The research utilized the PRISMA 2020 methodology to conduct a systematic review on the importance of AAHRPP (Association for the Accreditation of Human Research Protection Programs) accreditation in clinical research centers. The study reviewed and synthesized evidence to evaluate how AAHRPP accreditation influences the quality, safety, and effectiveness of clinical research. This study aims to explore the importance of accreditation processes in these centers, highlighting how standardized and rigorous evaluation practices enhance the care and conduct of clinical trials. The findings emphasize that AAHRPP accreditation promotes the adoption of strict standards for the protection of study participants, standardizes processes and procedures in research institutions, increases the credibility of accredited institutions, and facilitates international collaboration. Additionally, AAHRPP accreditation contributes to the continuous improvement of research protection programs, being essential to ensure regulatory compliance and ethics in the conduct of clinical studies.